Exploration of the solar system using multimedia technology - Devaraju, Anusuriya; Muniandy, Sucilia Devi; Maksom, Zulisman (2006)
One of the most rapidly changing and exciting areas of education today is the development of computer-based educational materials or courseware. The purpose of the project is to develop an educational courseware prototype that presents a vivid multimedia adventure unfolding the splendor of the Solar System. The targeted end-users of the courseware will be high-school classes, as well as non-science majors in introductory astronomy classes. The courseware enables students to discover the facts and phenomena of the Solar System through an archive of text, graphics, audio, videos, 2D and 3D animations. The courseware also includes self- asessment components can be integrated to provide the student with immediate feedback. The development of courseware is important in offering enhanced exploration and educational enjoyment of the Solar System and beyond. It provides a comprehensive self-learning and interactive material to the students via multimedia technology.